Patterns And Recurring Themes In The Music Of John Carpenter - Cundell, Tomasz Adam (2024)
Despite being one of the most popular cult film directors of the late twentieth century, very little has been written about John Carpenter’s work and even less about the scores that he wrote for his films. Indeed, landmark film scoring texts such as On The Track do not even mention his name among the hundreds of other composers they highlight. This research examines Carpenter’s film scores and later album work in order to find out what makes his music idiomatic: whether this be through similar musical themes or structures, or prevailing patterns and other consistent stylistic features that appear throughout his work. The research project starts from Carpenter’s film Dark Star (1974) and extends to his last feature film The Ward (2010) and will include his three Lost Themes albums and his scores for other directors, including Halloween (2018) and Firestarter (2022). It will look at these works and break cues down into basic musical fundamentals such as melody, timbre and rhythm, and also identify where and how Carpenter places these cues in the context of his films. Although the majority of Carpenter’s output consists of horror films, with a few exceptions such as Big Trouble In Little China (1986), an action film with elements of science-fiction, attention will be paid to how Carpenter uses or dismisses common genre tropes in his writing. Carpenter’s ostinato driven scores differ from the majority of contemporaneous film scores because they seem more akin to the pop and rock music of the time. However, elements of Carpenters scoring style can be seen in the works of composers such as Hans Zimmer and Michael Giacchino. This indicates that Carpenter’s scoring style aided in the popularisation of synthesizer-based film scoring and ostinato driven scores. His most heavily recognised cue, the theme for Halloween (1979), works around a 5/4 quaver pattern that drops a semitone and then rises again as the bass slowly creeps up a minor third and then a semitone. Carpenter’s father originally taught him the quaver pattern on a pair of bongos when he was a child which he later adapted into the iconic horror theme. Throughout the research will discover who Carpenter’s other influences were and how they affected the writing of his music. By contextualising Carpenter’s work and comparing it to the work of his peers in the film music industry an effort will be made to see how typical of the period Carpenter’s scores were. Films such as Forbidden Planet (1956), scored by Louis and Bebe Barron, will be compared to Carpenter’s body of work as Carpenter’s reliance on synthesizer-driven music can be seen as a natural progression from the early electronically scored films.